The Relationship of Facial Measurements with the Mesiodistal Width of the Maxillary Anterior Teeth - Aziz, Nur Ilyana Aifa; Che Mohd, Nadia; Baharuddin, Izyan Hazwani; Rajali, Aiemeeza; Lim, Tong Wah; Tan, Su Keng; Ahmad, Rohana (Journal of Dentistry Indonesia, 2021)
The relationship between facial measurements and the size of the maxillary anterior teeth in the Malaysian population is still a point of contention. Objective: The purpose of this study was to establish a relationship between facial measurements and the mesiodistal width of the maxillary anterior teeth (MDW), which could be used to guide the selection of anterior teeth for complete denture construction. Methods: The facial and dental measurements were obtained directly from 170 Malay adults aged between 19 to 35 who had morphologically normal permanent maxillary anterior teeth from canine to canine. The facial dimensions measured were interpupillary distance (IPD), intercanthal distance (ICD) and interalar distance (IAD). The facial dimensions were measured using a digital vernier calliper while the mesiodistal width of the maxillary anterior teeth was measured with a flexible ruler. The three facial dimensions were correlated with MDW for both genders. Results:The IPD and IAD were significantly (p>0.001) larger in males (IPD: 68.30±4.24mm; IAD: 39.60±2.54mm) than in females (IPD: 65.93±3.91mm; IAD: 36.96±2.29). There was no significant correlation between any of the facial dimensions and MDW in males or females. Conclusion: For the studied population, the interpupillary, intercanthal, and interalar distances may not be used as reliable guides when determining the size of maxillary anterior teeth in complete denture construction.